2022
DOI: 10.22495/cgobrv6i1p6
|View full text |Cite
|
Sign up to set email alerts
|

Corporate sustainability performance throughout the firm life cycle: Case of Egypt

Abstract: The role of corporations in society is an age-old debate among practitioners and academics. The corporations’ primary goal is to excel, prosper, and expand financially is no longer suitable for the community. Unfortunately, the need for financial prosperity leads to hazardous workplaces, chemical exposure, and urban decay. Therefore, companies now view internal and external corporate responsibility as a critical business strategy for sustainable management. Thus, examining the impact of firm life cycle stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 169 publications
0
3
0
Order By: Relevance
“…Through this process, access to resources and how management makes strategic decisions will also differ, ultimately shaping CSR activities and behavior (Lee & Choi, 2018). Gamal et al (2022) stated that a firm's life cycle has excellent explanatory power over a company's sustainability performance, and CSR initiatives should be integrated into company decisions and resource allocation. Diebecker (2017) finds that the sustainability performance of companies is lower before and after the firm's mature stage.…”
Section: Introductionmentioning
confidence: 99%
“…Through this process, access to resources and how management makes strategic decisions will also differ, ultimately shaping CSR activities and behavior (Lee & Choi, 2018). Gamal et al (2022) stated that a firm's life cycle has excellent explanatory power over a company's sustainability performance, and CSR initiatives should be integrated into company decisions and resource allocation. Diebecker (2017) finds that the sustainability performance of companies is lower before and after the firm's mature stage.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no specific information available about Gama Corporate's response to these challenges, companies in similar situations have adopted various strategies to ensure resilience and sustainability. Focusing on corporate sustainability performance (CSP) and corporate social responsibility (CSR) initiatives, which can help companies create long-term value and growth [7]. Adopting innovative strategies to improve financial performance and internal processes [8].…”
Section: Introductionmentioning
confidence: 99%
“…In line with the changes in organisational structures and financial decisions in terms of investments, reporting, financial planning, and dividends, a strand of academic literature has concluded that the respective life cycle stages and transitions between them have an impact also on the corporate governance mechanisms and social responsibility actions (Habib & Hasan, 2019). Evidence suggests a correlation between corporate sustainability practices and the life cycle stages of firms (Diebecker et al, 2017;Gamal et al, 2022). Adopting financial policies based on the life cycle stages also includes effects on ESG disclosure practices (Atif et al, 2022).…”
Section: Combining Corporate Life Cycle Stages With Corporate Sustain...mentioning
confidence: 99%